Special topics in structural dynamics. proceedings of the 34th IMAC, a Conference and Exposition on Structural Dynamics 2016 /: proceedings of the 34th IMAC, a Conference and Exposition on Structural Dynamics 2016. Volume 6 : (2016) - Unknown
No abstract available